THE ENERGY TRANSITION DILEMMA IN EUROPEAN UNION (EU) REGION - Mae Luky Iriani (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
The European Union has been facing an energy crisis since 2020 that is made worse by the extreme weather in winter and the hasty energy transition across mainland Europe. As the global world demands cleaner energy and renewable energy for all, the EU may have to strategize better to gradually shift from fossil fuel and anticipate the uncertainty and the volatility of renewable energy. This paper will examine the possible cause and sustainable solution to ensure the countries are still able to secure their environmental target, without severe consequences, economically and socially while maintaining their political legitimacy in dealing with Russia. The method used for this research includes a literature review. The outlook of the crisis will be depended on the securitization effort by the EU and solidarity amongst its members. EU will also still require fossil fuels to ease the transition to renewable energy in the coming years.